2021
DOI: 10.5114/ceji.2021.109827
|View full text |Cite
|
Sign up to set email alerts
|

Tim-1 alleviates lupus nephritis-induced podocyte injury via regulating autophagy

Abstract: Introduction:Lupus nephritis (Ln) is a complication of systemic lupus erythematosus (SLE) which seriously threatens the health of people. Tim-1 is known to be associated with the pathogenesis of SLE. however, the role of Tim-1 in Ln is still unclear.Aim of the study: To explore the expression and the potential regulatory molecular mechanism of Tim-1 in Ln-induced podocyte injury.Material and methods: an in vivo model of Ln was established to detect the expression of Tim-1, inflammatory cytokines and autophagy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…e average annual growth rates in recent years have reached 19.86%, 33.46%, and 25.37%, respectively, as shown in Figure 5 [15].…”
Section: Current Status Of Patients With Cardiovascular Disease (Cvd)mentioning
confidence: 95%
See 1 more Smart Citation
“…e average annual growth rates in recent years have reached 19.86%, 33.46%, and 25.37%, respectively, as shown in Figure 5 [15].…”
Section: Current Status Of Patients With Cardiovascular Disease (Cvd)mentioning
confidence: 95%
“…e partial derivatives of parameters α and β in formula (15) are calculated and set to 0 respectively, and the overall parameter estimate that maximizes ln [L(θ)] is obtained through the following formulas:…”
Section: Cvd Regression Model Logistic Regression Explores the Mappin...mentioning
confidence: 99%
“…Furthermore, upregulation of the CCAAT/enhancer‐binding protein β (C/EBP‐β) isoform was observed in LN patients and MRL/lpr mice, while the NLRP3 inflammasome is regulated by C/EBP‐β, indicating that it may regulate podocyte pyroptosis 92 . The inflammatory factors released by podocyte pyroptosis induce the proliferation of mesangial cells and the extensive secretion of collagen 93 . These converging lines of evidence underscore the central role of podocyte pyroptosis in LN.…”
Section: Pathophysiology Of Podocyte Injury and Death In Lnmentioning
confidence: 87%
“…The evidence showed that interleukin-1β (IL-1β) and IL-18 are involved in mesangial hyperplasia and pathogenesis of LN. The inflammatory factors released by pyroptotic podocytes could trigger mesangial cells to proliferate and secrete large amounts of collagen, leading to renal impairment in the progression of LN [24]. Therefore, we analyzed cleaved IL-1β and cleaved IL-18 in the conditioned media collected from podocytes of four groups.…”
Section: Silencing C/ebpβ Significantly Delays Ln Serum-induced Podoc...mentioning
confidence: 99%